2020
DOI: 10.7717/peerj.10472
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic paradox: domestic violence and happiness of women

Abstract: Background Across the globe, lockdowns have been enforced as a pandemic response to COVID-19. Such lockdown coupled with school closures and stay-at-home orders made women more vulnerable in terms of higher responsibility and spending more time with an abusive partner, if any. Methods This study investigates the situation of women during COVID-19 induced lockdown by focusing on their happiness and inquiring about the incidence of violence. Using the zero-inflated negative binomial model, our findings ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 13 publications
4
21
0
8
Order By: Relevance
“…Com relação a ocorrência de IPV durante a pandemia de COVID-19, observou-se que todos os estudos evidenciaram situações abusivas perpetradas pelo parceiro íntimo (Aolymat, 2021;Fawole et al, 2021;Gebrewahd et al, 2020;Gosangi et al, 2021;Haq, Raza & Mahmood, 2020;Krishnamurti et al, 2021;Mahmood et al, 2021;Naghizadeh, Mirghafourvand, Mohammadirad, 2021;Pattojoshi et al, 2021;Sabri et al, 2020). As taxas de IPV durante o período pandêmico variaram entre 18,1% na Índia (Pattojoshi et al, 2021) até 38,7% no Iraque (Mahmood et al, 2021).…”
Section: Características Dos Artigos Analisadosunclassified
See 1 more Smart Citation
“…Com relação a ocorrência de IPV durante a pandemia de COVID-19, observou-se que todos os estudos evidenciaram situações abusivas perpetradas pelo parceiro íntimo (Aolymat, 2021;Fawole et al, 2021;Gebrewahd et al, 2020;Gosangi et al, 2021;Haq, Raza & Mahmood, 2020;Krishnamurti et al, 2021;Mahmood et al, 2021;Naghizadeh, Mirghafourvand, Mohammadirad, 2021;Pattojoshi et al, 2021;Sabri et al, 2020). As taxas de IPV durante o período pandêmico variaram entre 18,1% na Índia (Pattojoshi et al, 2021) até 38,7% no Iraque (Mahmood et al, 2021).…”
Section: Características Dos Artigos Analisadosunclassified
“…As taxas de IPV durante o período pandêmico variaram entre 18,1% na Índia (Pattojoshi et al, 2021) até 38,7% no Iraque (Mahmood et al, 2021). No Irã (Naghizadeh et al, 2021) e no Paquistão (Haq et al, 2020) as pesquisas demonstraram uma prevalência de aproximadamente 35%, enquanto na Etiópia os casos de violência por parceiro íntimo representaram 24,6% (Gebrewahd et al, 2020) (Quadro 1).…”
Section: Características Dos Artigos Analisadosunclassified
“…Professional women spend additional time doing household responsibilities with their regular professions, as several productions and administrations have shifted their work at home level. Reports from various countries show that the increase in domestic violence is alarming (Haq et al, 2020).…”
Section: Distinct Clusters Needmentioning
confidence: 99%
“…Although both men and women are equally exposed to information and guidelines on such measures, women might be more prone to fully comply with them [19,20]. A study performed in Spain reported that women scored higher on perceived vulnerability than men [21], hence, exposing themselves less to transmission risks and more frequently following COVID-19 preventive protocols [22,23]. This common behavior after a disease threat may be ingrained in mental processes common to women, such as those described by the fi eld of developmental psychology [24].…”
mentioning
confidence: 99%